REITERATION IN STORYBOOK “THE THING IN THE DUNGEON” BY EMMA LAYBOURN - Tita, Tita Tita; Efransyah, Efransyah Efransyah (IKIP Siliwangi, 2020)
This study aims to see which types of reiteration are commonly occurred in the storybook entitled ''The Thing in the Dungeon'' by Emma Lay bourn. This study used descriptive qualitative research and used document analysis as a research instrument. The storybook is a book containing stories for children. The authors chose the storybook as research material because it has its structure that is intended specifically for children, and has a high number of viewers and ratings. The objectives of the research are to analyze the types of reiteration that mostly used in that storybook. From this research, the data presented sequentially 115 (93.4%) for repetition, 7 (5, 6) % for a synonym, and 1 (1%) for antonym. The writers didn’t found types of reiteration superordination which cover hyponym and metonym. After conducting research the researchers concluded that repetition is the most types of reiteration that are used in the storybook because they attract special attention to a certain message. The synonym is at the second and the last position is the antonym. Keywords: Reiteration, Lexical cohesion, Storybook